INNOVATING TRADITION: A MARKETING STRATEGY TO MODERNIZE TOFU PRODUCTION (A CASE STUDY OF H. ROHIM'S TOFU BUSINESS IN JEMBER) - Fitriyah, Lailatul; Farid, Achmad; Asshiddiqi, Hasbi (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study examines the marketing strategies and production processes at H. Rohim's Tofu Business in Jember, focusing on the challenges of modernizing traditional practices. This research utilizes a qualitative approach to understand the underlying factors affecting the business’s marketing strategies and operational processes. Interviews with the owner and employees reveal a tension between traditional and digital marketing methods. Despite efforts to use social media and improve packaging, the business has struggled to reach younger consumers, relying heavily on word-of-mouth and loyal customer networks for promotion. Observations indicate that production is manual, using local ingredients, and distribution is confined to local markets, with minimal use of digital platforms. The business's goals include expanding market reach and increasing production, but limited resources and resistance to change hinder the full implementation of these strategies. The study highlights the importance of blending traditional marketing techniques with innovative approaches to meet evolving market demands. The findings suggest that overcoming the company's reluctance to digitalize and invest in modern marketing strategies is crucial for its growth. This case underscores the challenges faced by small businesses in adapting to technological advancements while maintaining their traditional values.